Strengthening economic resilience Insights from the post-1970 record of severe recessions and financial crises - Caldera Sánchez, Aida (OECD Economic Policy Papers, 2017)
Considering the deep and long-lasting impact of severe recessions, such as the 2008-09 financial crisis, it is important that measures be taken to minimise the risk of such event. But in doing so the benefits need to be balanced against the potential costs in terms of lower average growth that some of the actions to lower vulnerabilities to bad events could entail. Insofar as the risk-mitigating measures can involve a trade-off between growth and crisis risk, the most cost-effective actions need to be identified, spanning both macro and structural policies. The work summarised in this paper has explored this issue using two complementary empirical approaches, both providing insights on the impact of various policy settings on average GDP growth on the one hand, and either crisis risks or GDP growth at the (negative) tail end, on the other. The results indicate that pro-growth product and labour market policies generally have little impact on the exposure to crisis. More significant tradeoffs between efficiency and crisis risk arise in the case of financial market policies